ANALISIS PENGETAHUAN MITIGASI BANJIR PADA MASYARAKAT KABUPATEN BANJAR DENGAN PENDEKATAN METODE REGRESI LOGISTIK BINER - Rahmadini, Rahmiyanti; Febrianty, Irma; Lilimantik, Emmy; Ferrianta, Yudi (Universitas Lambung Mangkurat, 2024)
The largest flood condition in South Kalimantan Province occurred in 2021. The worst flooded area is Banjar Regency with 27,249 fatalities. Floods also affected the agriculture and fisheries sectors, causing agricultural land productivity to decrease to 87,598 tons from 2021 to 2020. A total of 1,838 aquaculture businesses suffered losses of up to 70 billion rupiah. The causes of flooding do not only come from natural factors but can come from other factors such as a lack of knowledge of flood mitigation, resulting in huge losses for the community. Previous research states that the factors that influence flood disaster mitigation are the level of education and income. This study aims to determine the factors that influence flood mitigation knowledge in Banjar Regency communities using the binary logistic regression method. The results of the study provide differences from previous studies, namely the environmental factor with category 1, the implementation of environmental management by the community affects flood mitigation knowledge with a p value (0.027) < α (0.05) and a value of W (2.2198) > Z_table (1.960). The odds ratio value shows that the probability of the Banjar Regency community having flood mitigation knowledge is 2.79 times greater than other variable categories. The model explains an influence of 31.6% with an AIC value of 125. The respondents flood mitigation knowledge in managing the environment includes all types and stages of flood disaster mitigation related to local wisdom in the respondents location, namely several terms such as